Memória organizacional no contexto dos processos de gestão do conhecimento associados às práticas arquivísticas - Feitoza, Rayan Aramís de Brito (2019)
It is aimed to analyze how the processes of knowledge management associated to the archival practices can contribute with the formation and preservation of the organizational memory in the Service of Support to the Micro and Small Companies of Paraíba (SEBRAE/PB). Methodologically, it is an exploratory, descriptive and correlation study with qualitative approach. It is a documentary and field research, configured as a case study in the archive of the researched organization. It is adopted as technique and collection instrument the intensive direct observation with notes in a formalized field journal, as well as semi structured interview for validation, using content analysis as the technique of analysis and interpretation of data by means of a system of categories, subcategories, and indicators reasoned on national and international authors. The processes of knowledge management associated to the archival practices were identified from the following categories: selection, organization, storage and knowledge update. It is ratified that the SEBRAE/PB is an organization based on knowledge, considering its administrative structure, its documents of strategic level, as well as the actions of knowledge management identified in the analysis categories. In the organization, knowledge management is under the responsibility of the Unit of Marketing, Communication and Knowledge Management, and it is also responsible by the information inherent to the archive sector. It is noted that, although it does not occur in a continuous and integrated way, there are effective actions of processes of knowledge management together with the archival practices in the SEBRAE/PB. However, the organization needs to create guidelines or policies more consistent to the improvement of these processes, continuing the activities that collaborate to keep the organizational memory updated in the labor environment of their collaborators and clients. It is evidenced the dimensions of organizational memory in the context of the processes of knowledge management associated to the archival practices based on the obtained results in the research field and in the inferences. It is concluded that the processes of knowledge management, when associated to archival practices, contribute with the formation and preservation of the organizational memory, by means of strategies of sharing and creating of knowledge and of practices developed in the archival environment.